Gut Microbiota Dysbiosis Is Not Independently Associated With Neurocognitive Impairment in People Living With HIV - Zhang, Fengdi; Yang, Junyang; Ji, Yongjia; Sun, Meiyan; Shen, Jiayin; Sun, Jianjun; Wang, Jiangrong; Liu, Li; Shen, Yinzhong; Zhang, Renfang; Chen, Jun; Lu, Hongzhou (Frontiers in Microbiology, 2019)
Gut microbiota dysbiosis, which has been linked to many neurological diseases, is common in HIV infection. However, its role in the pathogenesis of neurocognitive impairment is still not established. In the current study, a total of 85 HIV infected subjects naïve to antiretroviral therapy were classified into two groups—those with HIV-associated neurological diseases (HAND) and those without, using the Montreal Cognitive Assessment (MoCA) test. Fecal samples were collected from all subjects and microbiota were analyzed by 16S rRNA amplicon sequencing. Subjects with HAND were older (P < 0.001), with lower levels of education (P = 0.002), lower CD4 T-cell counts (P = 0.032), and greater heterosexual preference (P < 0.001) than those without HAND. Gut microbiota from subjects with HAND showed significantly lower α-diversity compared to that from subjects without HAND (Shannon index, P = 0.003). To exclude confounding bias, 25 subjects from each group with comparable age, gender, CD4 T-cell count, educational level, and sexual preference were further analyzed. The two groups showed comparable α-diversity (for SOB index, Shannon index, Simpson index, ACE index, and Chao index, all with P value > 0.05) and β-diversity (ANOSIM statistic = 0.010, P = 0.231). There were no significant differences in microbiota composition between the two groups after correction for false discovery rate. Consistently, microbiota from the two groups presented similar predictive functional profiles. Gut microbiota dysbiosis is not independently associated with neurocognitive impairment in people living with HIV.